Analysis and design of a high-speed projector for environmentally sustainable micro and nanoparticle deposition. (23rd July 2007) - Jackson, Mark J.; French, R. Mark; Handy, Rodney G.; Tomovic, Mileta M.; Gorrepathi, Vinay; Alcorta, Eduardo
It may be possible to use high-speed impacts as a machining process at the meso and microscales. Before this can be realised, it is necessary to develop both an understanding of the physics of such impacts and to develop a method of generating repeatable, accurate impacts. As a first step in this process, we have made a simple device that fires small spheres at high-speed using the pressure differential generated by a vacuum. We have quantified the performance of a small-scale gas-gun by recording firing events using high-speed video. Experimental data is compared to results from numerical simulations to completely characterise the physics involved in firing. In addition, we present the results of high-speed impacts resulting in significant plastic deformation in the target material.